Differential geometry of intersection curve of two surfaces - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2009)
In this this article the differential geometry of intersection curve of two surfaces in the three dimensional euclidean space is considered.In case, curvature and torsion formulas for such curve are defined.